Strategy for renewal and transformation 2011 - 2014 (ACP Secretariat BrusselsBE, 2010)
Presents the strategic plan of the Secretariat of the African, Caribbean and Pacific (ACP) Group of States for the period 2011 - 2014.
Keywords: ACP